Oxidative Stress in Diabetic Retinopathy - Ortega, Ángel Luis (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The combination of an increasing prevalence of diabetes and the aging of populations enables the appearance of a greater number of associated complications such as diabetic retinopathy. Diabetic retinopathy is the leading cause of preventable vision loss in working-age adults. The objective of this Special Issue is to highlight the existing evidence regarding the relationship between oxidative stress and low-grade chronic inflammation induced by hyperglycemia with the development and progression of diabetic retinopathy, with an emphasis on the importance of early diagnosis and the use of antioxidant and anti-inflammatory approaches to prevent or delay the harmful effects of diabetes on retinal tissue.